Thyroid Dysfunction States and Incident Cardiovascular Events: The Tehran Thyroid Study - Tohidi, Maryam; Derakhshan, Arash; Akbarpour, Samaneh; Amouzegar, Atieh; Mehran, Ladan; Baghbani-Oskouei, Aidin; Azizi, Fereidoun; Hadaegh, Farzad (Hormone and Metabolic Research, 2018)
The objective of the study was to investigate the relation of different thyroid function states with the incidence of cardiovascular disease (CVD)/coronary heart disease (CHD) among a Middle-Eastern population with a high incidence of CVD/CHD. A total of 3975 participants entered the study (43.6% men). According to their thyroid stimulating hormone (TSH) and free thyroxin (FT4) levels, the participants were categorized into 5 groups: euthyroid, subclinical hypothyroidism, overt hypothyroidism, subclinical hyperthyroidism, and overt hyperthyroidism. Multivariable Cox proportional hazard models were used to assess the relation of different thyroid function states with incident CVD/CHD, with euthyroid state as reference. The mean age (SD) of the participants was 46.5 (12.0) years. At baseline, no significant difference was observed in the frequency of prevalent CVD cases (n=201) between all groups. No significant interaction was found between prevalent CVD and different thyroid function states with outcomes, hence, we did not exclude participants with prevalent CVD from data analysis. A total of 400 CVD events (358 CHD cases) during a median follow-up of 11.2 years (inter-quartile range: 1.96) occurred. During the follow-up, even in the age and sex adjusted model, no association was observed between different states of thyroid dysfunction and incidence of CVD/CHD. The multivariable hazard ratios (95% CI) of subclinical hypothyroidism, hypothyroidism, subclinical hyperthyroidism, and hyperthyroidism for CVD events were 1.21 (0.77–1.88), 0.76 (0.33–1.69), 0.81 (0.46–1.41) and 1.48 (0.70–3.16), respectively. Both at baseline and during follow-up, no relation was observed between different states of thyroid function with prevalence and incidence of CVD/CHD.
Keywords: hypothyroidism; hyperthyroidism; cardiovascular disease; subclinical